A Plan for Academic Biobank Solvency—Leveraging Resources and Applying Business Processes to Improve Sustainability. Issue 5 (21st May 2015) - Uzarski, Diane; Burke, James; Turner, Barbara; Vroom, James; Short, Nancy
Abstract: Researcher‐initiated biobanks based at academic institutions contribute valuable biomarker and translational research advances to medicine. With many legacy banks once supported by federal funding, reductions in fiscal support threaten the future of existing and new biobanks. When the Brain Bank at Duke University's Bryan Alzheimer's Disease Center (ADRC) faced a funding crisis, a collaborative, multidisciplinary team embarked on a 2‐year biobank sustainability project utilizing a comprehensive business strategy, dedicated project management, and a systems approach involving many Duke University entities. By synthesizing and applying existing knowledge, Duke Translational Medicine Institute created and launched a business model that can be adjusted and applied to legacy and start‐up academic biobanks. This model provides a path to identify new funding mechanisms, while also emphasizing improved communication, business development, and a focus on collaborating with industry to improve access to biospecimens. Benchmarks for short‐term Brain Bank stabilization have been successfully attained, and the evaluation of long‐term sustainability metrics is ongoing.